PERAN NEGARA DALAM PELAYANAN INVESTASI ASING DI KOTA BATAM TAHUN 2017 - Claudia, Yunia; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The role of the State through Batam Indonesia Free Zone Authority (BIFZA) as the Central Government in the are of Batam City in the context of creating an invesment climate and increasing economic growth in Batam, the Riau Island and the national. Batam Indonesia Free Zone Authority (BIFZA) has a strong legal basis and this is stated in Government Regulation Number 46 of 2007 concerning the Free Trade Zone and Batam Free Port. This research uses a qualitative approach. Data was collected using stakeholder elements in Batam Island in 2017. Data were collected through informants purposively. Data collection techniques using field research, interviews and documentation studies. While data analysis uses the process of reducing, presenting and verifying data. The results of the discussion show that first, the dualism of authority between the Batam Indonesia Free Zone Authority (BIFZA) and the Batam City Government in legal uncertainty in Batam City, where Batam is currently being discouraged as initially a Free Trade Zone (FTZ) or Free Trade Zone towards a Special Economic Zone (KEK) . This causes doubts about the investors who will invest their capital in Batam. So this will have an impact on economic growth both in Batam City, Riau Islands and National. Secondly, the role of the State through the Batam Business Entity in managing the increase of foreign investment in the City of Batam in 2017. In this case the Batam Indonesia Free Zone Authoruty in creating a good investment climate so as to realize economic growth in the city of Batam. Keywords: Dualism of Authority, Foreign Investment, Batam City